EFFECT OF FLY ASH AND RICE HUSK ASH ON STRENGTH CHARACTERISITCS OF PAVEMENT QUALITY CONCRETE - Singh, Amrinder Pal (My University, 2013)
There is growing interest in the construction of concrete pavements, due to its high strength, durability, better serviceability and overall economy in the long run. The thrust nowadays is to produce thinner and green pavement sections of better quality, which can carry the heavy loads. The high strength is a concrete having compressive strength greater than 40MPa, made of hydraulic cements and containing fine and coarse aggregates; The present study aims at, developing pavement quality concrete mixtures incorporating fly ash and rice husk ash partial replacement of cement. The aim is to the design of slab thickness of PQC pavement using the achieved flexural strength of the concrete mixtures. In this study, compressive and flexural strength for pavement quality concrete mixtures for different percentage replacement of cement are reported. It is found that it is possible to achieve savings in cement by replacing it with fly ash. This study also shows that in view of the high flexural strength, high values of compressive strength the 20% replacement of cement with flyash is ideal for design of Pavement Quality Concrete (PQC).
ME, CED
Keywords: Fly ash; Rice husk ash; Pavement Quality Concrete; Strength; Flexure; PQC